O impacto do processo de financeirização sobre a estrutura social nas empresas: estudo de caso no setor elétrico paulista - Matsuda, Patricia Mari (2015)
With the process of financialization of the economy, companies are reorganizing themselves. In front of this, the present work has as main objective observe the process of financialization and its impact on the social structure of a company that went through the privatization process. Also, analyze in the corporate environment, (the new) forms of organizational management and production, as well its key actors and their forms of interrelationship. This work is based on Political Economics, with studies in the financialization process rooted in culture, history and policy of a company that has undergone in a series of transformations. This research develops how the company changes its conception of control, and how this change has an impact in its overall structure. Thus, the scope of this work focused on an exploratory study in Eletropaulo. The central importance of the study in the Brazilian electric sector is that this sector has undergone to the most radical changes in the financialization since 1990. However, any research on the built of the executive s careers, in this Brazilian context, has been done so far. The analysis of curriculum is the most important contribution from this case study research. As a research procedure of this work, were combined quantitative and qualitative methods. In order to analyze the careers of executives of AES Eletropaulo, were collected the curriculum of the Board and Directors, since its appearance as state-owned company in 1979 to the year 2012. It is applied a cumulative frequency analysis and other correspondence multiple analysis to study these curricula. Also, to see how the company was restructured as a whole after the change of ownership, were used other qualitative tools, such as questionnaires and interviews to key players in the buying and selling process. To develop this thesis, the case study will be separated into three parts. In the first are analyzed and presented data, in the form of graphs, related to the performance indicators of the company's case over his years before and after privatization. The second part is related to the new organizational management, which refers to the shareholding after the sale of the company, thus, opens up the discussion to the internationalization of ownership and National Development Bank in Brazil - BNDES, being the major shareholders of AES Eletropaulo an international company and BNDES. And in the third, the focus is on the analysis of the careers of executives of this company, and how they constructed and reconstructed their careers after major changes. As result, it was observed that the case company has undergone a series of transformations, including the creation of a new identity. The Government acts in two different moments at the same company. It is observed in this study that the pressure of these new owners have consequences in organizational design and composition of the power of the company to a search for maximization of the value of the company. And the executives of the company had to find ways to rebuild their careers in accordance with the new financial logic at the moment. The present analysis also extends to the electricity utility workers and their vulnerabilities occurred by the financialization process.